The Role of Central Bank in the Recession in the Case of Japan's Recession - Shigeyoshi Miyagawa; Yoji Morita; Yoshitaka Sawada (Aboa Centre for Economics (ACE), 2007)
Japan's economy is expanding and expected to continue expanding moderately, according to Monthly Report of Recent Economic and Financial Developments released by the Bank of Japan in July 2007.The BOJ declared the change of policy stance at the Monetary Policy Meeting held on July 14, 2006. The BOJ had to tackle a recession which the Japanese economy had not experienced before. The economy was on the verge of financial panic, especially in 1997 and 1998, when major financial institutions had failed. It reminded us of the recurrence of the Great Depression in the 1930s. The article will clarify how the Japanese economy fell into a serious depression with a reflection on the role of the BOJ in the emergence of prolonged depression. We will also estimate the interest rate elasticity of money demand in order to identify whether or not the Japanese economy was in a liquidity trap in the prolonged recession. We will use the EGARCH model to quantify the financial anxieties. The conclusion will suggest that the BOJ should have paid more attention to the behavior of money stock at the early stage of depression.
Keywords: E21; E22; E24; E44; 330; bubble; money stock; financial anxieties; liquidity trap